Q: What is 5y equal to?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

The expression -5y + 6 is a combination of a variable (y) and constants (-5 and 6) connected by addition and subtraction operations. To find the answer, you would need a specific value for the variable y. Without knowing the value of y, the expression -5y + 6 cannot be simplified further.

5y=25x 25x=5y -5y 25x-5y=0

5y

5y-3y = 2

If the inequality is > (greater than) or >= (greater than or equal to), then there are an infinite number of solutions. So let the inequality be < (less than) or <= (less than or equal to) x = 1: 5y <= 16 so y = 1, 2 or 3 x = 2: 5y <= 12 so y = 1 or 2 x = 3: 5y <= 8 so y = 1 x >= 4: 5y <= 4 no solution. So whether the inequality is < or <= there are 6 ordered pairs.

Related questions

0

It equals x+5y simplified

5y + 24 = 29 5y = 5 (subtract 24 from both sides) y = 1 (divide by 5)

-8-5y = 12-9y 9y-5y - 12+8 4y = 20 y = 5

-8x-5y-45 is not an equation. An equation requires an equal sign in there somewhere. If you meant -8x-5y=45, then there are many ways to rewrite it, such as -(8x+5y)=45, or 8x+5y=-45, or 8x=-(45+5y), to name three. If you meant -8x-5y=-45, then you're probably looking for 8x+5y=45.

The expression -5y + 6 is a combination of a variable (y) and constants (-5 and 6) connected by addition and subtraction operations. To find the answer, you would need a specific value for the variable y. Without knowing the value of y, the expression -5y + 6 cannot be simplified further.

no, 4x-3y=11x 3x-5y doesn't equal -11

6y + 5y = -66 11y = -66 (-66/11 = y) y = -6

-3

If 3x, 5y and 7z are equal terms, them each of them will equal one third of 357, or 119. 3x = 119 x = 39 and 2/3 5y = 119 y = 23 and 4/5 7z = 119 z = 17

5Y - X = 11 ( the 1 coefficient is always implied, not written )5Y = X + 11Y = (1/5)X + 11/5m(slope) = 1/5===========

5y + 5y = 10y